1995
DOI: 10.3109/10408449509017924
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Compounds in Relation to Breast Cancer, Endometrial Cancer, and Endometriosis: An Assessment of the Biological and Epidemiological Evidence

Abstract: There is an increasing public and scientific concern that certain chlorinated compounds, recognized as environmental pollutants, may cause estrogen-related neoplastic disease in humans. The main hypothesis has been that certain organochlorines, through their estrogenic actions, might cause breast cancer. From experimental studies, both in vitro and in vivo, there is evidence that certain organochlorine compounds may cause estrogenic effects, whereas others may cause antiestrogenic effects. In limited studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(164 citation statements)
references
References 216 publications
3
159
2
Order By: Relevance
“…It is possible the relevant organochlorine exposure measure for breast cancer risk might be the woman's body burden at critical periods of breast susceptibility and that current levels do not represent these exposures. Both lactation and body mass index impact levels of organochlorine compounds (6,7). We found no evidence that either factor influenced any relationship of PCBs or DDE and breast cancer risk.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It is possible the relevant organochlorine exposure measure for breast cancer risk might be the woman's body burden at critical periods of breast susceptibility and that current levels do not represent these exposures. Both lactation and body mass index impact levels of organochlorine compounds (6,7). We found no evidence that either factor influenced any relationship of PCBs or DDE and breast cancer risk.…”
Section: Discussioncontrasting
confidence: 56%
“…The organochlorine residues present at the highest concentrations in human adipose tissue, breast milk and blood are dichlorodiphenyldichloroethene (DDE), the metabolite of the pesticide dichlorodiphenyltrichloroethane (DDT), and the non-pesticide class of polychlorinated biphenyls (PCBs) (6). Extensive evidence exists from animal studies of the carcinogenicity of DDT, DDE and PCBs (7). Exposure to DDT and PCBs in mice has each resulted in an increased incidence of cancers of the liver and lung, as well as of lymphoma and leukemia (6,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…the Baltic Sea) is contaminated by persistent organochlorine compounds (POCs). Indeed, this fish an important source of exposure to POCs in the Swedish population (10)(11)(12). Previous studies had found that Swedish fishermen and their families on average consume more fish than the general Swedish population (10,13,14).…”
Section: Fishermen's Wivesmentioning
confidence: 99%
“…Attention has focused an environmental and dietary oestrogens as possible contributors to the increased incidence of breast cancer but the epidemiological findings are inconclusive (Ahlborg et al, 1995;Safe, 1995). However, even though the total amount of environmental and dietary oestrogen is low, it might have an influence over time, especially in adolescent women.…”
Section: Survivalmentioning
confidence: 99%